2003
DOI: 10.1016/s0925-4439(03)00127-3
|View full text |Cite
|
Sign up to set email alerts
|

Functional alteration of cytochrome c oxidase by SURF1 mutations in Leigh syndrome

Abstract: Subacute necrotising encephalomyopathy (Leigh syndrome) due to cytochrome c oxidase (COX) deficiency is often caused by mutations in the SURF1 gene, encoding the Surf1 protein essential for COX assembly. We have investigated five patients with different SURF1 mutations resulting in the absence of Surf1 protein. All of them presented with severe and generalised COX defect. Immunoelectrophoretic analysis of cultured fibroblasts revealed 85% decrease of the normal-size COX complexes and significant accumulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(44 citation statements)
references
References 51 publications
5
39
0
Order By: Relevance
“…29 Indeed, a similar increase in the protein content of CcO was observed in human fibroblasts with a selectively reduced content of complex I holoenzyme. 30 The observed discrepancy between the cytochrome oxidase activity and ascorbate/TMPD-driven respiration was reported 31 and probably stems from different preparations of the enzyme complex. Unlike the lowconcentration digitonin treatment (respirometry), which preserves the inner membrane intact, the lauryl maltoside solubilization (spectrofotometric CcO assay) removes the enzyme complex from the inner membrane, eventually leading to altered enzyme function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…29 Indeed, a similar increase in the protein content of CcO was observed in human fibroblasts with a selectively reduced content of complex I holoenzyme. 30 The observed discrepancy between the cytochrome oxidase activity and ascorbate/TMPD-driven respiration was reported 31 and probably stems from different preparations of the enzyme complex. Unlike the lowconcentration digitonin treatment (respirometry), which preserves the inner membrane intact, the lauryl maltoside solubilization (spectrofotometric CcO assay) removes the enzyme complex from the inner membrane, eventually leading to altered enzyme function (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…In the myocardial tissue homogenate, maximal ADP-stimulated oxidative capacity of mitochondria was determined as oxygen consumption rate with palmitoylcarnitine (12.5μM)+malate (3mM)+glutamate (10mM)+succinate (10mM) using high-resolution oxygraph-2k (OROBOROS, Austria) [30]. Respiratory control index that indicates the tightness of the coupling between respiration and phosphorylation was calculated as the ratio of glutamate+malate+ADP (1.5mM) respiration without and with oligomycin (6μM).…”
Section: Mitochondrial Functionmentioning
confidence: 99%
“…Comparable studies revealed subcomplexes of OXPHOS complexes III-V including those from patients and mutants with defects in assembly factors (e.g. [234][235][236][237][238][239]). In some cases, the formation of aberrant aggregates in vivo from remnant subunits of protein complexes may be also conceivable.…”
Section: Migration Shift Analysis In Native Pagementioning
confidence: 99%
“…Concomitantly, besides ATP synthase oligomers high yields of stoichiometric supercomplexes (III 2 IV 1 and III 2 IV 2 ) of the yeast respiratory complexes III and IV were separated and identified from digitonin extracts applied to BN-PAGE [107,145,149,174,[305][306][307][308] and CN-PAGE [107,111]. Likewise, the same approach resulted in the detection of ATP synthase dimers and specific supercomplexes of complexes I, III and IV preserved by digitonin solubilization of mitochondria from bovine heart [60,110,145,146,159] and other mammalian tissues [104,110,112,156,235,309,310], the filamentous fungus Podospora anserina [108], and higher plants [109,147,148,311]. Analysis by the more gentle CN-PAGE was reported to improve the yields of preserved OXPHOS supercomplexes from fungi and mammals [107,108,110,112,120], but not from higher plants [109].…”
Section: Oxphos Supercomplexes In Mitochondriamentioning
confidence: 99%